Answer:
7.1
,
8.1
,
9.1
Explanation:
The terms of an arithmetic sequence are generated by adding the common difference (d) to the previous term.
a
1
,
a
1
+
d
,
a
1
+
2
d
,
a
1
+
3
d
,
...
.
,
a
1
+
(
n
−
1
)
d
where
d
=
a
2
−
a
1
=
a
3
−
a
2
=
...
.
=
a
n
−
a
n
−
1
here
d
=
4.1
−
3.1
=
1
Adding 1 to each term gives the next 3 terms in the sequence.
⇒
(
6.1
+
1
)
=
7.1
and so onThe terms of an arithmetic sequence are generated by adding the common difference (d) to the previous term.
a
1
,
a
1
+
d
,
a
1
+
2
d
,
a
1
+
3
d
,
...
.
,
a
1
+
(
n
−
1
)
d
where
d
=
a
2
−
a
1
=
a
3
−
a
2
=
...
.
=
a
n
−
a
n
−
1
here
d
=
4.1
−
3.1
=
1
Adding 1 to each term gives the next 3 terms in the sequence.
⇒
(
6.1
+
1
)
=
7.1
and so onThe terms of an arithmetic sequence are generated by adding the common difference (d) to the previous term.
a
1
,
a
1
+
d
,
a
1
+
2
d
,
a
1
+
3
d
,
...
.
,
a
1
+
(
n
−
1
)
d
where
d
=
a
2
−
a
1
=
a
3
−
a
2
=
...
.
=
a
n
−
a
n
−
1
here
d
=
4.1
−
3.1
=
1
Adding 1 to each term gives the next 3 terms in the sequence.
⇒
(
6.1
+
1
)
=
7.1
and so onThe terms of an arithmetic sequence are generated by adding the common difference (d) to the previous term.
a
1
,
a
1
+
d
,
a
1
+
2
d
,
a
1
+
3
d
,
...
.
,
a
1
+
(
n
−
1
)
d
where
d
=
a
2
−
a
1
=
a
3
−
a
2
=
...
.
=
a
n
−
a
n
−
1
here
d
=
4.1
−
3.1
=
1
Adding 1 to each term gives the next 3 terms in the sequence.
⇒
(
6.1
+
1
)
=
7.1
and so onThe terms of an arithmetic sequence are generated by adding the common difference (d) to the previous term.
a
1
,
a
1
+
d
,
a
1
+
2
d
,
a
1
+
3
d
,
...
.
,
a
1
+
(
n
−
1
)
d
where
d
=
a
2
−
a
1
=
a
3
−
a
2
=
...
.
=
a
n
−
a
n
−
1
here
d
=
4.1
−
3.1
=
1
Adding 1 to each term gives the next 3 terms in the sequence.
⇒
(
6.1
+
1
)
=
7.1
and so on